PENGARUH SALINITAS TERHADAP TINGKAT KELANGSUNGAN HIDUP DAN PROFIL DARAH IKAN NILA (OREOCHROMIS NILOTICUS) YANG DIBERI KOMBINASI PAKAN DAN BUAH MENGKUDU (MORINDA CITRIFFOLIA L.) - Andriyan, Muhammad Fajar; Rahmaningsih, Sri; Firmani, Ummul (Jurnal Perikanan Pantura (JPP), 2018)
Tilapia (Oreochromis niloticus) is one type of freshwater fish that is very popular in thecommunity. In the body of tilapia fish have a close relationship with salinity. Adaptation oftilapia is physiological adaptation to high salinity range because tilapia belong to fish euryhaline.This study aims to analyze good salinity on survival rate and blood profile of tilapia fed withnoni fruit. The method used was experimental method with Completely Randomized Design(CRD), 4 treatments with 3 replications ie control treatment (0 ppt), treatment A (5 ppt),treatment B (10 ppt), C treatment (15 ppt). The parameters observed were survival rate and bloodprofile of tilapia. Data analysis by using Analysis of Variance (ANOVA) to know the influenceof each treatment. If the data has been analyzed variance there is a real difference, then followedby Tuckey test at 95% test level. The largest red blood profile in treatment A with the amount ofErythrocite at the end of the study was 3.660.000 cells / mm-3. The highest white blood profile intreatment C with an average number of Leukocytes 55,900 cells / mm-3. The best media salinityfor survival rate in this study was 5 ppt salinity.